Macroscopic modeling of turbulent flow over a porous medium - Chan, H.C.; Huang, W.C.; Leu, J.M.; Lai, C.J. (The International journal of heat and fluid flow, 2007)
Turbulent flow over a porous medium has been one of the most critical subjects in numerous environmental and engineering studies. The characteristics associated with the hybrid domain, involving both a porous region and a clear fluid region, are not fully understood primarily due to a lack of proper mathematical treatments of different regions and the fluid/porous interface. The objective of this study is to present a numerical implementation for examining such a hybrid domain. The governing equations were solved by a control volume method and the k– ε turbulent model in an attempt to predict the turbulent stresses. The present model treated the hybrid domain problem with a single domain approach by adopting the classical continuity interface conditions. Our numerical results were compared with the experimental data available in the literature for two cases. The effects of the porous medium on the flow properties, including porosity and permeability, were further investigated. Moreover, the calculated flow features were examined for three different Reynolds numbers. Results indicated that the penetration extent of turbulence was Darcy number- and porosity-dependent.